2017
DOI: 10.3390/s17092134
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Textile Nanocomposite as Naked Eye Indicator of the Exposition to Strong Acids

Abstract: Chemical burns, mainly produced by acids, are a topic of concern. A new sensing material for the detection of strong acids able to be incorporated into textiles has been developed. The material is prepared by the covalent attachment of 2,2′,4,4′,4″-pentamethoxy triphenyl methanol to a mesoporous material which further is included in a nitro resin to obtain a colourless composite. The response of this composite to diverse acid solutions was tested showing the appearance of an intense purple colour (with a colou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…Silica-based colorimetric nanosensors can be incorporated into polymers and textiles, benefiting from the combination of nanomaterials with a macroscopic support. A novel naked eye sensing probe was developed for the detection of strong acids combining chemical pH indicators, textile fabrics, and mesoporous silica [23]. Silica nanoparticles were functionalized with 2,2′,4,4′,4″-pentamethoxy triphenyl methanol (pentamethoxy red pH indicator).…”
Section: Systems Based On Dyes and Reactive Units Grafted Onto Surmentioning
confidence: 99%
“…Silica-based colorimetric nanosensors can be incorporated into polymers and textiles, benefiting from the combination of nanomaterials with a macroscopic support. A novel naked eye sensing probe was developed for the detection of strong acids combining chemical pH indicators, textile fabrics, and mesoporous silica [23]. Silica nanoparticles were functionalized with 2,2′,4,4′,4″-pentamethoxy triphenyl methanol (pentamethoxy red pH indicator).…”
Section: Systems Based On Dyes and Reactive Units Grafted Onto Surmentioning
confidence: 99%
“…Moreover, the dye is anionic due to the sulphonic group present in the dye molecule. Even though the MO dye was not developed for the dyeing of cellulosic fibres, the studies showed that applying different indicator dyes assures the formation of pH-sensitive cellulosic textiles [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Current studies have mentioned several methods of application of pH-responsive dyes to textiles, namely conventional dyeing [5,6,[10][11][12][13][14][15], spraying [16], direct incorporation of the dye during electrospinning [7,12,17,18], coating [19,20], and sol-gel technology [8,12,21], but only one study mentioned conventional printing [22]. Halochromic behaviour of pH-responsive dye is in close correlation to dye structure [10,12], presence of different substituents in dye molecule [6], fibre composition [11,12], type of dye-fibre interactions [12], fabric density [10], and application methods [12].…”
Section: Introductionmentioning
confidence: 99%